Digital innovation and social adaptation in urban flood risk reduction: A study on community-based coping strategies - Putri, Sapta Dwi (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: Flooding in the capital city of DKI Jakarta is still a serious problem that has a broad impact on society. Rapid urbanization, suboptimal drainage systems, and climate change contribute to the increasing frequency and impact of flooding. Flooding not only causes economic losses, but also impacts on health, loss of livelihoods, agriculture and livestock sectors, disruption to education, and damage to public and private infrastructure, effective strategies are needed to increase community resilience in the face of these disasters. Methods: This study used a methodological approach related to coping strategies in the face of flooding. The theory of coping strategies developed by Lazarus & Folkman (1984) is used as the basis of analysis to understand how communities can adapt and respond to floods. In addition, a study of digital platforms such as petabencana.id was conducted to see the role of technology in improving community preparedness. Findings: The results show that communities use various copingstrategies in dealing with floods, both those that focus on problem-focused coping and those that focus on emotion-focused coping. Technology-based approaches, such as the use of petabencana.id, allow communities to share information in real-time, improve coordination in emergency response, and speed up decision-making in disaster situations. This research also highlights the importance of a combination of proactive and reactive coping strategies in dealing with floods. In addition, utilizing digital technology in disaster mitigation can increase the effectiveness of emergency response efforts and strengthen community engagement. Conclusion: This study confirms that the application of appropriate coping strategies, supported by technology and multi-stakeholder collaboration, can help communities deal more effectively with the impacts of flooding. Novelty/Originality of this article: Increasing education on coping strategies, optimizing the use of information technology, and strengthening social networks are important steps in flood mitigation and management in Jakarta.